Rare bird documentation form for Glaucous Gull at Lock and Dam 15, 1983 - Petersen, Peter C.et al (1983)
Rare bird documentation form for a Glaucous Gull at Lock and Dam 15 in Davenport in Scott County, IA on January 23, 1983 and January 25, 1983. Epson - sheet feed